A Variety of Nucleic Acid Species Are Sensed by cGAS, Implications for Its Diverse Functions - Wang, Dawei; Zhao, Heng; Shen, Yangkun; Chen, Qi (Frontiers in Immunology, 2022)
Cyclic GMP-AMP synthase (cGAS) recognizes double-stranded DNA (dsDNA) derived from invading pathogens and induces an interferon response via activation of the key downstream adaptor protein stimulator of interferon genes (STING). This is the most classic biological function of the cGAS-STING signaling pathway and is critical for preventing pathogenic microorganism invasion. In addition, cGAS can interact with various types of nucleic acids, including cDNA, DNA:RNA hybrids, and circular RNA, to contribute to a diverse set of biological functions. An increasing number of studies have revealed an important relationship between the cGAS-STING signaling pathway and autophagy, cellular senescence, antitumor immunity, inflammation, and autoimmune diseases. This review details the mechanism of action of cGAS as it interacts with different types of nucleic acids, its rich biological functions, and the potential for targeting this pathway to treat various diseases.